The spirit of Korean development - Yu, Sang-yŏng (Seoul Yonsei University Press, 2015)
The book divides Korea's developmental trajectory into four stages: economic growth, democratization, informtization, and smart power, and analyzes how these four aspects formed a virtuous cycle and advanced.
1. Exploring the spirit of Korean development: origins -- 2. Examining the spirit of development: a historical overview -- 3. Economic development and the historical memory of poverty -- 4. Democratization and cultural genomes for democracy and human rights -- 5. Informatization, globalization, and nomadic dynamism -- 6. Toward a smart power in the international context -- 7. Conclusion: challenges and the future of Korean development.
Includes bibliographical references (pages 116-125) and index.
Keywords: Economic development -- Social aspects -- Korea (South); Economic development -- Social aspects; Korea(South).